Guzarish va musavvabati hijdahumin kungirahi-yi kunfidrasyuni jahani : (Kunfidrasyuni Jahani-yi Muhassilin va Danishjuyani Irani (ittihadyahi-yi Milli), 1977)
The report and resolutions of the Eighteenth Congress of the World Confederation, Frankfurt 4-13/1/1977. Kurdistan Democratic Party of Iran.